2012
DOI: 10.1177/0969733011433923
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional analysis of ethical climate, job satisfaction, organizational commitment, and organizational citizenship behaviors

Abstract: The high turnover of nurses has become a global problem. Several studies have proposed that nurses' perceptions of the ethical climate of their organization are related to higher job satisfaction and organizational commitment and thus lead to higher organizational citizenship behaviors. This study uses hierarchical regression to understand which types of ethical climate, facets of job satisfaction, and the three components of organizational commitment influence different dimensions of organizational citizenshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
171
2
29

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(237 citation statements)
references
References 66 publications
(101 reference statements)
16
171
2
29
Order By: Relevance
“…Moreover, Katrinliet al, (38) found job involvement is an important construct that is correlated with different work behaviors and outcomes such as performance& OCB.As well as Huang et al, (2) argued that hospitals could increase the levels of OCB for nurses by strengthening their organization's ethical climate, job satisfaction, and organizational commitment. In addition Chen et al, (39) found strong evidence exists that organizational support and organizational identification positively affect OCB in nursing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Katrinliet al, (38) found job involvement is an important construct that is correlated with different work behaviors and outcomes such as performance& OCB.As well as Huang et al, (2) argued that hospitals could increase the levels of OCB for nurses by strengthening their organization's ethical climate, job satisfaction, and organizational commitment. In addition Chen et al, (39) found strong evidence exists that organizational support and organizational identification positively affect OCB in nursing.…”
Section: Resultsmentioning
confidence: 99%
“…Concepts aimed at increasing the performance of nurses who play a key role in delivery of healthcare services, have an importance in increasing the efficiency of organizations (1) .Therefore, human resource and management professionals have become interested in the concept of organizational citizenship behavior because they considered improving nurses Organizational Citizenship Behavior(OCB) is a crucial factor for developing organizations. Organizational citizenship behavior improves efficiency and nurses' involvement and generally provides a healthy work environment (2) .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, bank employee respondents completed the three-item caring climate scale developed by Huang, You, and Tsai (2012), who adapted the scale from Victor and Cullen (1988). The items were as following: The most important concern is the good of all the people in the hospital as a whole; What is best for everyone in the hospital is the major consideration here; Our major concern is always what is best for the other person.…”
Section: Instruments and Measuresmentioning
confidence: 99%
“…On the other hand, JS and organizational commitment are frequently explored together. Some studies have showed that JS has an important effect on organizational commitment (Fu & Despande, 2013;Huang, You & Tsai, 2012). However, according to Grdinovac and Yancey's (2012) proposals, employees of organizations that use more caring adaptations have a greater affective organizational commitment than the employees of organizations that use fewer caring adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of this article it is suggested that their definition be used as the overall definition of ethical climate. Their definition largely captures the essence of the definitions and opinions of the various scholars mentioned before (Mayer et al, 2010;DeConinck, 2011;Deshpande et al, 2011;Guerci, et al, 2015;Huang et al, 2012;Hwang & Park 2014), as it focuses on the mutual aspects of firstly "shared perceptions and norms", secondly in terms of what is considered to be "ethically correct behaviour" and lastly the handling of ethical issues in an organisation in general (Victor & Cullen, 1987:51-52). They extended their definition to define ethical climate as "the prevailing perceptions of typical organisational practices and procedures that have ethical content" (Victor & Cullen, 1988:101).…”
Section: The Construct 'Ethical Climate'mentioning
confidence: 99%